Improved diagnosis of farmer's lung using the fluorescent antibody technique. Issue 4 (July 1974) - Boyd, G.; Parratt, D.
Abstract : Boyd, G. and Parratt, D. (1974). Thorax, 29, 417-420. Improved diagnosis of farmer's lung using the fluorescent antibody technique. In the west of Scotland 20 of 40 farmers surveyed had symptoms of farmer's lung. Ten of this group (50%) gave positive precipitin reactions to Micropolyspora faeni. The fluorescent antibody test was positive in all those with symptoms and also in one who had no clinical evidence of farmer's lung. There was a close relationship between evidence of sensitization to M. faeni in the serum, demonstrated by the fluorescent antibody test, and the presence of symptoms compatible with farmer's lung. This test may detect the disease in milder form than is possible by conventional precipitin tests and this study confirms the value of this more sensitive technique as a screening procedure.